Membaca Narasi Penciptaan Mazmur 19:1-6 Melalui Perspektif Kosmologi Intelligent Design: Irreducible Complexity - Yahya Afandi (Sekolah Tinggi Teologi Baptis, Jakarta, 2020)
This article examines: is science and theology so wide apart from each other; is the suffering of bible scholars who have a